Bibliometric analysis of scientific publications on the effects of rangeland and wild plants on women's health - Tufan, Yasir; Tufan, Zeynep (Womens Health & Action Research Centre, 2025)
This study presents a comprehensive bibliometric assessment of global research on the use of rangeland and wild plants in women's health from 1996 to 2025. A total of 718 publications retrieved from Web of Science and Scopus were analysed using the Bibliometrix/Biblioshiny platform. Descriptive indicators, co-occurrence networks, thematic evolution, clustering, and Multiple Correspondence Analysis (MCA) were used to map structural and conceptual trends in the field. The findings indicate a steady increase in scientific output, with an annual growth rate of 11.02%. Publications were concentrated in core journals such as Phytomedicine and Journal of Ethnopharmacology, while Iran, India, and China were the leading contributing countries. Keyword and conceptual analyses showed that traditional knowledge, medicinal plants, phytochemistry, and pharmacology form the central research axis. Notably, themes related to women's health-particularly menopause, pregnancy, infertility, polycystic ovary syndrome, and endometriosis-appeared consistently across trend, thematic, and cluster analyses, indicating a stable and growing research focus. The study highlights the multidimensional nature of ethnopharmacology at the intersection of ecosystem-derived plant resources, cultural knowledge, and clinically relevant women's health research, underscoring the need for broader geographic representation and interdisciplinary integration in future studies. (Afr J Reprod Health 2025; 29 [12s]: 149-164).
Keywords: Medicinal Plants; Female Reproductive System; Reproductive Health; Ethnopharmacology; Natural Vegetation